Comprehensive river basin development : the Tennessee Valley Auth ority - Reidinger, Richard B.; Miller, Barbara A. (Washington, D.C. : The World Bank, 1998)
Based on papers presented at a World Bank sponsored seminar held on Feb 13, 1997 in Washington, D.C.
Includes bibliographical references (p. 75-76).
Keywords: Tennessee Valley (Tex) -- History; Water resources development -- Tennessee Valley (Tex)